Enhancing cybersecurity in Bank Syariah Indonesia: Strategi menjaga data nasabah dan mencegah serangan cyber - Anam, M. Yusfil (Maliki Interdisciplinary Journal, 2023)
Cybersecurity has emerged as a paramount concern in the modern banking industry, particularly in the wake of the cyberattack involving Bank Syariah Indonesia (BSI) that led to significant losses for the bank and its customers. This article delves into strategies that financial institutions can adopt to bolster their defense systems against cyber threats, with a focus on safeguarding customer data and preempting cyber attacks. Through an in-depth review of literature and analysis, we present an array of strategies, including the implementation of information security technologies such as Security Operation Centers (SOCs) and sensitive data encryption, along with the adoption of a zero trust model, Global Private Network (GPN), and the integration of blockchain technology into banking IT systems. We also examine the role played by the Financial Services Authority (OJK) through its regulations and guidelines in reinforcing resilience and cybersecurity within the banking sector. This article offers profound insights into the necessary endeavors to mitigate cybersecurity risks within the banking realm, with the aspiration of incentivizing banks to embrace holistic and proactive strategies in navigating cyber risks and safeguarding invaluable customer data.